Inflation hedging for long-term investors - Attié, Alexander P.; Roache, Shaun K. (IMF working paper ;, 2009)
Long-term investors face a common problem-how to maintain the purchasing power of their assets over time and achieve a level of real returns consistent with their investment objectives. While inflation-linked bonds and derivatives have been developed to hedge the effects of inflation, their limited supply and liquidity lead many investors to continue to rely on the indirect hedging properties of traditional asset classes. In this paper, we assess these properties over different time horizons, in the context of a diversified portfolio. Using a vector error correction model, we find that effecti.